Digitalization of investment-innovative activities of the trade business entities in network IT-system - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Yeremenko, Denys; Єременко, Денис Володимирович; Еременко, Денис Владимирович; Karman, Serhii; Карман, Сергій Вікторович; Карман, Сергей Викторович; Kolokolchykova, Iryna; Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; et al. (My University, 2021)
The problem of digital business transformation through innovative development in the country, which affects the transformation of business structures, including trade, remains underdeveloped, which requires further scientific, methodological, practical research and justification. The priority of this study is to develop a system-integrated methodology and practical recommendations for building a model of digitization of investment-innovative activities of the trade entities by transforming the architecture of the business system into an IT-system, which demonstrates improving network interaction in a competitive environment. The article considers the digitalization of investment-innovative activities of the trade entities in the network IT system. The system-integrated methodology is implemented and practical recommendations are offered to build a model of digitalization of investment-innovative activities of the trade entities by transforming the architecture of the business system into an IT system, which demonstrates the efficiency of network interaction in a competitive environment. The block diagram of the activation of Digital-strategy of digitalization of investment-innovative development of business in economy is presented. A block system for evaluating the digitalization of investment-innovative activities of the trade entities in the network IT system is proposed. Indicators of digitalization of investment-innovative activities of the trade entities in the network IT system are grouped according to the components of the balanced scorecard (CFS). The architectural structure of the integrated indicator of the zonal level of digitalization of investment-innovative activities of the trade entities in the network IT system is substantiated. The coordinates of the vector-standard of zonal digitization of investment-innovative activities of the trade entities in the network IT system of Ukraine are determined.
Keywords: business processes; IT-outsourcing; global market; technologies; zonal level